2019
DOI: 10.1021/acs.est.9b05641
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Secondary Brown Carbon in Biomass Burning Aerosol Proxies through NO3 Radical Reactions

Abstract: Atmospheric brown carbon (BrC) is an important contributor to the radiative forcing of climate by organic aerosols. Because of the molecular diversity of BrC compounds and their dynamic transformations, it is challenging to predictively understand BrC optical properties. OH radical and O3 reactions, together with photolysis, lead to diminished light absorption and lower warming effects of biomass burning BrC. The effects of night-time aging on the optical properties of BrC aerosols are less known. To address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
157
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(169 citation statements)
references
References 80 publications
9
157
0
Order By: Relevance
“…IR absorption by BrC has been measured in a few studies. While Li et al (2020) found negligible absorption for wood tar aerosol above 550 nm, Sumlin et al (2018b) did find a small amount of absorption, k = 0.002 ± 0.005, for 1047 nm light in smoke from smoldering peat fires in a laboratory. That absorption is only sufficient to heat 300 nm particles by about 25°C (Fig.…”
Section: Aerosol Sampling During Oraclesmentioning
confidence: 93%
See 1 more Smart Citation
“…IR absorption by BrC has been measured in a few studies. While Li et al (2020) found negligible absorption for wood tar aerosol above 550 nm, Sumlin et al (2018b) did find a small amount of absorption, k = 0.002 ± 0.005, for 1047 nm light in smoke from smoldering peat fires in a laboratory. That absorption is only sufficient to heat 300 nm particles by about 25°C (Fig.…”
Section: Aerosol Sampling During Oraclesmentioning
confidence: 93%
“…BC is a hypothetical material that absorbs more or less as a black body and includes graphitic soot nanospheres and amorphous C. BrC is organic material that absorbs light primarily at short wavelengths (Andreae and Gelencser, 2006) and to a small and very poorly known extent in the IR (e.g. Li et al, 2020;Sumlin et al, 2018b). Tarballs (Pósfai et al, 2003(Pósfai et al, , 2004 are a distinctively spherical variety of BrC prevalent in aged biomass burning plumes.…”
Section: A Note About Black Carbonmentioning
confidence: 99%
“…However, the temporal continuity in atmospheric aging processes is generally overlooked, and most studies focus on a single reaction pathway in BB-BrC aging or ignore the modifications due to diel atmospheric transformations altogether in climate models. 15 , 16 , 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“… 26 28 Such wood tar aerosols have been applied in a number of recent studies to investigate the atmospheric aging of BB-BrC in the laboratory. 16 , 20 , 28 30 …”
Section: Introductionmentioning
confidence: 99%
“…Negative ESI‐FT‐ICR MS was applied to characterize molecules in ambient aerosols and smoke particles (Brege et al, 2018; Jiang et al, 2016; Mazzoleni et al, 2012; Song et al, 2018, Zhang et al, 2018). However, direct applications of ESI FT–ICR MS on studying BrC optical properties, such as exploring the relationship between absorption and molecules, are still very limited (Laskin et al, 2018; Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%